Blazing a Trail…or Blazing Saddles: A Case Study of Players' Social Media Response to the Decision to Drop UAB Blazer Football. Issue 3 (1st September 2016) - Hull, Kevin; Lee, Jason W.
Abstract : In 2014, the University of Alabama-Birmingham (UAB) elected to eliminate its football team, citing rising costs. This case study examines how the players on that team used Twitter as a tool for crisis communication, specifically the #FreeUAB hashtag, in order to demonstrate their opposition to that decision. An analysis of over 1300 tweets from 44 players revealed that while players primarily used the hashtag when discussing the team, they also utilized it in a variety of other tweet topics. Additionally, the majority of the tweets posted to the players' accounts were retweets from other accounts, demonstrating that the players preferred to show the support from others instead of voicing their own opinions. Implications regarding stakeholder social media communication during a crisis are discussed.